2007
DOI: 10.1186/1475-9276-6-23
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and decomposing inequity in self-reported morbidity and self-assessed health in Thailand

Abstract: Background: In recent years, interest in the study of inequalities in health has not stopped at quantifying their magnitude; explaining the sources of inequalities has also become of great importance. This paper measures socioeconomic inequalities in self-reported morbidity and self-assessed health in Thailand, and the contributions of different population subgroups to those inequalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
75
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 29 publications
8
75
1
2
Order By: Relevance
“…This means that if the marginal effect of a factor is large, but no inequalities exist in the distribution of that factor then its contribution to overall inequality will be low. Conversely, if a factor is concentrated amongst participants differentiated by their SES and the marginal effect of the factor is large then its contribution to the overall concentration index will be large (Yiengprugsawan et al, 2007).…”
Section: Measuring Socio-economic Inequalitymentioning
confidence: 99%
See 1 more Smart Citation
“…This means that if the marginal effect of a factor is large, but no inequalities exist in the distribution of that factor then its contribution to overall inequality will be low. Conversely, if a factor is concentrated amongst participants differentiated by their SES and the marginal effect of the factor is large then its contribution to the overall concentration index will be large (Yiengprugsawan et al, 2007).…”
Section: Measuring Socio-economic Inequalitymentioning
confidence: 99%
“…The original decomposition method assumes an underlying Ordinary Least Squares (OLS) regression model (Wagstaff et al, 2003); however, decomposition analyses can be undertaken with dichotomous outcomes if based on a linear approximation of the model (O'Donnell et al, 2008;Yiengprugsawan, Lim, Carmichael, Dear, & Sleigh, 2010;Yiengprugsawan, Lim, Carmichael, Sidorenko, & Sleigh, 2007). We used marginal effects derived from a probit model to produce an additive/linear approximation of the model, as expressed by the formula:…”
Section: Measuring Socio-economic Inequalitymentioning
confidence: 99%
“…Children typically consume less than adults, so counting children as adults may overestimate the living standards of households with children. For developing countries such as Indonesia, empirical studies recommend that a child aged under 15 should be modeled as costing roughly half of what an adult costs (α = 0.5) Yiengprugsawan et al 2007). In addition, household members can share certain types of goods and services, making these consumables cheaper in households of two or more persons than in one-person households.…”
Section: Methodsmentioning
confidence: 99%
“…Various studies have indicated that incidence of cancer varies across socio-economic position (SEP) groups and health disparities exist between and within countries even within cities (Yiengprugsawan et al, 2007;IAEA, 2011). Social, economical, environmental and political factors have been apparently known as the stem of inequalities in health.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the role of socioeconomic determinant of health (SDH) helps implement appropriate interventions to reduce disparities. Socioeconomic characteristics such as income, wealth, education, occupation, social class, and insurance coverage are potential indicators for comparison of different groups based on health and social features (Braveman et al, 2001;Yiengprugsawan et al, 2007;Natale-Pereira et al, 2011). The proportion of cancer incidence across SEP is dissimilar by cancer types; while some cancers are more common in higher socioeconomic positions such as prostate and breast cancers, a variety of cancers prevail in lower SEP groups such as lung and cervical cancers (Yin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%